2010
DOI: 10.4314/ijbcs.v4i2.58169
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical characteristics of oil and biodiesel from Nigerian and Indian <i>Jatropha curcas</i> seeds

Abstract: The oil and biodiesel produced from Nigerian and Indian Jatropha curcas seeds were evaluated using a parametric Student's t-test model. The characteristics assessed include oil yield, specific gravity, density, acid value, free fatty acid, iodine value, saponification value, peroxide value, viscosity and flash point. The results revealed significant differences (p < 0.05) between the yield of the Nigerian and Indian Jatropha oils (80% vs 56%). The acid value, free fatty acid, iodine value, peroxide and viscosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 4 publications
(1 reference statement)
3
9
1
1
Order By: Relevance
“…Accordingly, Kaushik et al [20] reported values of kinematic viscosity at 30°C for Jatropha oil from different countries (Variety Capeverde-39cSt, Variety Nicaragua37cSt and Variety Nigeria-17cSt). Similarly, a number of authors have carried out research works on Nigerian jatropha curcas oil from different locations across the country and obtained, to some extent, varying physicochemical properties and fatty acid composition depicted in references [19,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Kaushik et al [20] reported values of kinematic viscosity at 30°C for Jatropha oil from different countries (Variety Capeverde-39cSt, Variety Nicaragua37cSt and Variety Nigeria-17cSt). Similarly, a number of authors have carried out research works on Nigerian jatropha curcas oil from different locations across the country and obtained, to some extent, varying physicochemical properties and fatty acid composition depicted in references [19,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…A lot of research has been directed to modify oils to meet specific applications: as biodiesel (Lim and Lee, 2011;Sarin et al, 2010;Belewu et al, 2010, Rashid et al, 2010 *Corresponding author. E-mail: lm.nwokocha@mail.ui.edu.ng.…”
Section: Introductionmentioning
confidence: 99%
“…J. curcas plant found in Nigeria has the potential of boosting the economy in term of biodiesel production (Belewu et al, 2010). n-Hexane may be preferable in the extraction of biodiesel oil from J. curcas (Belewu et al, 2010), although petroleum ether had been used with lower yield (Adebayo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%